2020
DOI: 10.1080/15476286.2020.1804698
|View full text |Cite
|
Sign up to set email alerts
|

MCPIP1 ribonuclease can bind and cleave AURKA mRNA in MYCN -amplified neuroblastoma cells

Abstract: The role of the inflammation-silencing ribonuclease, MCPIP1 (monocyte chemoattractant proteininduced protein 1), in neoplasia continuous to emerge. The ribonuclease can cleave not only inflammation-related transcripts but also some microRNAs (miRNAs) and viral RNAs. The suppressive effect of the protein has been hitherto suggested in breast cancer, clear cell renal cell carcinoma, osteosarcoma, and neuroblastoma. Our previous results have demonstrated a reduced levels of several oncogenes, as well as inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 62 publications
(147 reference statements)
0
12
0
Order By: Relevance
“…Inhibits AURKA transcription Destabilizes AURKA mRNA [30] Cdh1 Induces AURKA degradation Cdh1-APC/C-ubiquitin-proteasome pathway.…”
Section: Mcpip1mentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibits AURKA transcription Destabilizes AURKA mRNA [30] Cdh1 Induces AURKA degradation Cdh1-APC/C-ubiquitin-proteasome pathway.…”
Section: Mcpip1mentioning
confidence: 99%
“…SIX3, a member of the sine oculis homeobox transcription factor family, suppresses the transcription of both AURKA and AURKB by directly binding with their promoters in astrocytoma [29]. Apart from the regulation of AURKA transcription through interaction with AURKA promoter, it was reported that ribonuclease MCPIP1 destabilized AURKA mRNA [30]. A highly conserved 95-base region in AURKA 3′-UTR was required for MCPIP1dependent cleavage of the AURKA transcript [30].…”
Section: Smad4mentioning
confidence: 99%
See 1 more Smart Citation
“…Data were analyzed as depicted earlier, 29 with a significance level threshold after correction for multiple testing set as 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Reverse transcription and RT‐qPCR for miRNAs was performed as described previously 29 . Primers for miRNA‐193a‐5p (YP00204665) and the reference miRNA‐103a‐3p (YP00204063) were purchased from Exiqon.…”
Section: Methodsmentioning
confidence: 99%